ABOUT THE SETTLEMENTS OF THE MİDDLE BRONZE AGE OF KARABAKH, AGTEPE AND SARYJALYTAYİ - Valiyeva, Gunel (SWorldJournal, 2024)
The article examines the archaeological sites of the Middle Bronze Age of Karabakh — the settlements of Agtepe and Saryjalytayi. The main attention is paid to their historical and cultural significance, chronological features and typology of the discovere